2021
DOI: 10.18860/jia.v6i4.11702
|View full text |Cite
|
Sign up to set email alerts
|

Design Framework for Ablution Spaces of Iconic Mosques in Malaysia

Abstract: Mosques are places where Muslims perform prayers and other social activities. Those are built as a place for humans to worship the Almighty Allah at all times, as well as to provide an environment that responds to the needs of devotees and educates the future generation by the Quranic verses and the Prophet's teachings. Derived from the Holy Quran and the Prophet, purity is compulsory at all times for Muslims, and has many meanings that are applicable during prayers and the day. The ablution room is integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…In line with the previous study, the research results strengthen the novelty of the topic of Iconic mosques. The Ministry of Tourism, Art, and Culture in Malaysia (MOTAC) classifies mosques as iconic buildings because mosques have high historical values and architectural styles that represent the aesthetics and modernity of the country [7]. As for the criteria for the Old Mosque of South Sulawesi, it has historical value, including Al-Hilal Katangka Gowa Old Mosque, Jami Tua Palopo Mosque, and Lamuru Bone Mosque [8].…”
Section: Methodsmentioning
confidence: 99%
“…In line with the previous study, the research results strengthen the novelty of the topic of Iconic mosques. The Ministry of Tourism, Art, and Culture in Malaysia (MOTAC) classifies mosques as iconic buildings because mosques have high historical values and architectural styles that represent the aesthetics and modernity of the country [7]. As for the criteria for the Old Mosque of South Sulawesi, it has historical value, including Al-Hilal Katangka Gowa Old Mosque, Jami Tua Palopo Mosque, and Lamuru Bone Mosque [8].…”
Section: Methodsmentioning
confidence: 99%
“…Facility management is also important to consider. A study by Utaberta and Shakir (2021) on mosques considered tourist attractions in Malaysia and found that some tourists lacked awareness of the function of the ablution space, mistaking it for a space to urinate. This highlights the need for clarifying signage and monitoring by facility management.…”
Section: Design Considerations For the Ablution Spacementioning
confidence: 99%
“…Some F 42,15/16 facilities resort to providing ablution areas at the basement level, which also raises the issue of hygiene because of the limited natural ventilation provided. Sunlight and natural airflow were also found essential to avoiding the spread of disease and fungus in the ablution rooms (Utaberta and Shakir, 2021). Wind directions need to be considered to prevent the transfer of humidity and humidity-related bad smells to the praying space.…”
Section: Design Considerations For the Ablution Spacementioning
confidence: 99%